Comparative Study to Evaluate Efficacy & Cost Effectiveness of Olmesartanversus Telmisartan, In Patients of Stage I Hypertension - Pankaj Kumar Singh; Sameer Kumar (Asian Journal of Medical Research, 2020)
Background: Hypertension is one of the most common diseases in the world. It is an important and independent risk factor for atherosclerosis, heart failure, renal disease, and peripheral arterial disease. It is directly responsible for 57% of all stroke deaths and 42% of coronary heart disease deaths in India. Aims and Objectives: To evaluate and compare efficacy and cost effectiveness in hypertensive patients receiving Olmesartan and Telmisartan in Stage I hypertensionSubjects and Methods:The present study was an open, prospective, randomized, parallel group comparative study conducted in 60 patients of stage I hypertension over a period of 16 weeks. Patients were randomly allocated to two, age and sex, matched groups of 30 patients each. Group I patients were started on Olmesartan at a dose of 20 mg & Group II patients were put on Telmisartan at a dose of 40 mg. The BP lowering efficacy and cost effective analysis of Olmesartan versus Telmisartan was calculated & compared. The data was entered in Microsoft excel and compiled. Statistical analysis was done using various tests.Results:Maximum patients in both the groups were in age group of 51-60 years. In group I there were 13 males and 17 females. In group II there were 14 males and 16 females. Both Olmesartan and Telmisartan are effective in lowering systolic & diastolic BP in supine & sitting positions & mean BP is also lowerer, more in Olmesartan group. By cost effective analysis Telmisartan was found more cost effective. Incremental cost effective ratio was found to be 218.35.Conclusion: Both Olmesartan and Telmisartan belong to the same antihypertensive drug class, effectively reduce systolic and diastolic blood pressure at various visits. Taking into account Total cost Telmisartan was more cost effective than Olmesartan. ICER was found to be 218.35.